Batteries Thermal Management for Hybrid plug-in Powertrains. Issue 1 (1st December 2022) - Perrone, D.; Falbo, L.; Castiglione, T.; Ficarella, A.; Bova, S.
Abstract: Lithium-ion batteries have become the primary battery technology used for electric and hybrid vehicles powertrains. Battery temperature, however, is a critical factor for these devices, as it influences battery performance life-time and safety and must be preferably kept in the 15-35 °C range. A dynamic electro-thermal model of a lithium iron phosphate battery was developed. The model predicts battery voltage and temperature evolution in different operating conditions. A battery equivalent circuit model (ECM) with an open circuit voltage source, an ohmic resistance and a capacitor-resistor pair in series is adopted. The state-of-charge is determined by the Coulomb counting approach and the battery temperature is computed by carrying out an energy balance for the cell. The balance takes into account the difference between the heat generated within the cell and the heat loss to the environment. Finally a controller, which cools or heats the battery in order to keep its temperature in the desired range, was developed. The case of the battery pack of a hybrid plug-in powertrain during a WLTP cycle is simulated and the result of different environmental conditions are presented.